Mortality among Tennessee Eastman Corporation (TEC) uranium processing workers, 1943–2019. (1st February 2023) - Boice, John D.; Cohen, Sarah S.; Mumma, Michael T.; Golden, Ashley P.; Howard, Sara C.; Girardi, David J.; Ellis, Elizabeth D.; Bellamy, Michael B.; Dauer, Lawrence T.; Eckerman, Keith F.; Leggett, Richard W.
Abstract: Background: There are few occupational studies of women exposed to ionizing radiation. During World War II, the Tennessee Eastman Corporation (TEC) operated an electromagnetic field separation facility of 1152 calutrons to obtain enriched uranium ( 235 U) used for the Hiroshima atomic bomb. Thousands of women were involved in these operations. Materials and methods: A new study was conducted of 13, 951 women and 12, 699 men employed at TEC between 1943 and 1947 for at least 90 days. Comprehensive dose reconstruction techniques were used to estimate lung doses from the inhalation of uranium dust based on airborne measurements. Vital status through 2018/2019 was obtained from the National Death Index, Social Security Death Index, Tennessee death records and online public record databases. Analyses included standardized mortality ratios (SMRs) and Cox proportional hazards models. Results: Most workers were hourly (77.7%), white (95.6%), born before 1920 (58.3%), worked in dusty environments (57.0%), and had died (94.9%). Vital status was confirmed for 97.4% of the workers. Women were younger than men when first employed: mean ages 25.0 years and 33.0 years, respectively. The estimated mean absorbed dose to the lung was 32.7 mGy (max 1048 mGy) for women and 18.9 mGy (max 501 mGy) for men. The mean dose to thoracic lymph nodes (TLNs) was 127 mGy. Statistically significant SMRs were observed for lung cancer (SMR 1.25; 95% CI 1.19, 1.31; n  = 1654), nonmalignant respiratory diseases (NMRDs) (1.23; 95% CI 1.19, 1.28; n  = 2585), and cerebrovascular disease (CeVD) (1.13; 95% CI 1.08, 1.18; n  = 1945). For lung cancer, the excess relative rate (ERR) at 100 mGy (95% CI) was 0.01 (–0.10, 0.12; n  = 652) among women, and −0.15 (–0.38, 0.07; n  = 1002) among men based on a preferred model for men with lung doses <300 mGy. NMRD and non-Hodgkin lymphoma were not associated with estimated absorbed dose to the lung or TLN. Conclusions: There was little evidence that radiation increased the risk of lung cancer, suggesting that inhalation of uranium dust and the associated high-LET alpha particle exposure to lung tissue experienced over a few years is less effective in causing lung cancer than other types of exposures. There was no statistically significant difference in the lung cancer risk estimates between men and women. The elevation of certain causes of death such as CeVD is unexplained and will require additional scrutiny of workplace or lifestyle factors given that radiation is an unlikely contributor since only the lung and lymph nodes received appreciable dose.